2019
DOI: 10.48550/arxiv.1912.02253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heavy Quarkonium in Extreme Conditions

Alexander Rothkopf

Abstract: In this report we review recent progress achieved in the understanding of heavy quarkonium under extreme conditions from a theory perspective. Its focus lies both on quarkonium properties in thermal equilibrium, as well as recent developments towards a genuine real-time description, valid also out-of-equilibrium. We will give an overview of the theory tools developed and deployed over the last decade, including effective field theories, lattice field theory simulations, modern methods for spectral reconstructi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 306 publications
(603 reference statements)
2
30
0
Order By: Relevance
“…Quarkonia are considered as a thermometer of medium produced in heavy-ion collisions and the fate of quarkonia states in the medium as well as transport coefficients are among the main topics in LQCD studies in extreme conditions [4,42]. Many new theoretical results obtained since last years' QM conference is overviewed in Ref.…”
Section: Quarkonia and Charm And Bottom Quark Drag Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quarkonia are considered as a thermometer of medium produced in heavy-ion collisions and the fate of quarkonia states in the medium as well as transport coefficients are among the main topics in LQCD studies in extreme conditions [4,42]. Many new theoretical results obtained since last years' QM conference is overviewed in Ref.…”
Section: Quarkonia and Charm And Bottom Quark Drag Coefficientsmentioning
confidence: 99%
“…A first continuum extrapolated results of J/ψ and Υ correlation functions have been obtained in quenched lattice QCD very recently [46]. The continuum extrapolation makes the direct comparison with pQCD computations possible, and thus alternatively from using inversion methods [42,47,48], the spectral functions are investigated by fitting to the correlators using a pQCD motivated ansatz [49]. It was found that no J/ψ peak is needed in the fit ansatz to describe the lattice correlator data T ≥ 1.1T c , while a resonance peak is still needed for Υ up to 1.5 T c as shown in the middle plot of Fig.…”
Section: Quarkonia and Charm And Bottom Quark Drag Coefficientsmentioning
confidence: 99%
“…To gain information on heavy quarkonium properties such as thermal modifications of bound states or transport coefficients, studies of the hadronic spectral function in the hot medium are needed [1,2]. On the lattice we cannot measure the spectral function directly, but instead calculate Euclidean correlators.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods for this ill-posed extraction problem have been proposed, for a recent review see [1]. In our approach, we compare continuum extrapolated correlators obtained from fine quenched lattices to a perturbative spectral function, constructed by combining vacuum asymptotics with pN-RQCD calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Since Matsui and Satz proposed the suppression of quarkonium in relativistic heavy-ion collisions as a signature of the quark-gluon plasma formation due to color screening [1], this phenomenon has been investigated in numerous theoretical and experimental studies (see, for instance, the recent review in Ref. [2]). One of the most critical quantities affecting quarkonium suppression is the potential between a heavy quark and anti-quark.…”
Section: Introductionmentioning
confidence: 99%